Longitudinal Evaluation of Cerebellar Signs of H-ABC Tubulinopathy in a Patient and in the taiep Model - Alata, Milvia; González-Vega, Arturo; Piazza, Valeria; Kleinert-Altamirano, Anke; Cortes, Carmen; Ahumada-Juárez, Juan C.; Eguibar, Jose R.; López-Juárez, Alejandra; Hernandez, Victor H. (Frontiers in Neurology, 2021)
Hypomyelination with atrophy of the basal ganglia and cerebellum (H-ABC) is a central neurodegenerative disease due to mutations in the tubulin beta-4A (TUBB4A) gene, characterized by motor development delay, abnormal movements, ataxia, spasticity, dysarthria, and cognitive deficits. Diagnosis is made by integrating clinical data and radiological signs. Differences in MRIs have been reported in patients that carry the same mutation; however, a quantitative study has not been performed so far. Our study aimed to provide a longitudinal analysis of the changes in the cerebellum (Cb), corpus callosum (CC), ventricular system, and striatum in a patient suffering from H-ABC and in the taiep rat. We correlated the MRI signs of the patient with the results of immunofluorescence, gait analysis, segmentation of cerebellum, CC, and ventricular system, performed in the taiep rat. We found that cerebellar and callosal changes, suggesting a potential hypomyelination, worsened with age, in concomitance with the emergence of ataxic gait. We also observed a progressive lateral ventriculomegaly in both patient and taiep, possibly secondary to the atrophy of the white matter. These white matter changes are progressive and can be involved in the clinical deterioration. Hypomyelination with atrophy of the basal ganglia and cerebellum (H-ABC) gives rise to a spectrum of clinical signs whose pathophysiology still needs to be understood.